Speciation of Cu, Cd, Pb and Zn in a contaminated harbor and comparison to environmental quality standards. (1st September 2022) - Layglon, Nicolas; Abdou, Melina; Massa, Francesco; Castellano, Michela; Bakker, Eric; Povero, Paolo; Tercier-Waeber, Mary-Lou
Abstract: The water column of harbors contains significant amounts of (priority) hazardous trace metals that may be released into coastal areas of high societal and economic interests where they may disturb their fragile equilibria. To deepen our understanding of the processes that influence the transport of the various metal fractions and allow for a more rigorous environmental risk assessment, it is important to spatially monitor the relevant chemical speciation of these metals. It is of particular interest to assess their so-called dynamic fraction, which comprises the dissolved chemical forms that are potentially bioavailable to living organisms. In this study this was achieved in the Genoa Harbor (NW Italy) for copper (Cu), lead (Pb), cadmium (Cd) and zinc (Zn) by applying a multi-method approach. For the first time in this system the dynamic fractions of the target metals (CuDyn, CdDyn, PbDyn, ZnDyn ) were observed in real-time on-board by voltammetry using innovative electrochemical sensing devices. Trace metals in the operationally defined dissolved <0.2 μm and <0.02 μm fractions were equally quantified through sampling/laboratory-based techniques. The obtained results showed a clear spatial trend for all studied metals from the enclosed contaminated part of the harbor towards the open part. The highest CuDyn and CdDyn fractions were found in the inner part of the harbor while the highest PbDyn fraction was found in the open part. The proportion of ZnDyn was negligible in the sampled area. Small and coarse colloids were involved in Cu, Cd and Zn partitioning while only coarse colloids played an important role in Pb partitioning. The determined concentrations were compared to the Environmental Quality Standards (EQS) established by the EU and those determined by the Australia and New Zealand to trigger for 99 and 95% species protection values. The results of this work allow us to highlight gaps in the EQS for which metal concentration thresholds are excessively high or non-existent and should urgently be revised. They also reflect the need to quantify the potentially bioavailable fraction of hazardous trace metals instead of just their total dissolved concentrations. The data support the establishment of environmental quality standards and guidelines based on realistic risk assessment to protect aquatic life and resources and ultimately human health. Highlights: On-board simultaneous detection of the bioavailable fraction of Cu, Cd, Pb and Zn. The proportion of bioavailable metal depends on the studied metals. Spatial variation of the bioavailable target metal species is site dependent. Coarse and small colloids influence Cu, Cd, Pb and Zn speciation. Bioavailable and dissolved Cu concentrations surpassed ANZECC 99% trigger value.